Overview of Proteus mirabilis pathogenicity and virulence. Insights into the role of metals - Chakkour, Mohamed; Hammoud, Zeinab; Farhat, Solay; El Roz, Ali; Ezzeddine, Zeinab; Ghssein, Ghassan (Frontiers in Microbiology, 2024)
Proteus mirabilis is a Gram-negative bacterium with exclusive molecular and biological features.It is a versatile pathogen acclaimed for its distinct urease production, swarming behavior, and rapid multicellular activity. Clinically, P. mirabilis is a frequent pathogen of the human urinary system where it causes urinary tract infections (UTIs) and catheter-associated urinary tract infections (CAUTIs). This review explores the epidemiology, risk factors, clinical manifestations, and treatment of P. mirabilis infections, emphasizing its association with UTIs. The bacterium's genome analysis revealed the presence of resistance genes against commonly used antibiotics, an antibiotic-resistant phenotype that poses a serious clinical challenge. Particularly, the emergence of extended-spectrum β-lactamases (ESBLs) and carbapenemases resistant P. mirabilis strains. On a molecular level, P. mirabilis possesses a wide array of virulence factors including the production of fimbriae, urease, hemolysins, metallophores, and biofilm formation. This review thoroughly tackles a substantial gap in understanding the role of metallophores in shaping the virulence factors of P. mirabilis virulence. Siderophores, iron metal chelating and transporting metallophores, particularly contribute to the complex pathogenic strategies, displaying a potential target for therapeutic intervention.